RESPON PERTUMBUHAN DAN PRODUKSI SAWI ( Brassica juncea L ) TERHADAP PEMBERIAN URINE KELINCI DAN PUPUK GUANO - Teuku Alvin Djafar; Asil Barus Asil Barus; Syukri Syukri (Universitas Sumatera Utara, 2013)
Farm waste recycling have a role in prevent cause of environment pollute, and in other side canincrease of plant production. One thing which real enough that a lot of farm waste can changebecame organic fertilizer. This reasearch is proposed to find out effect of growth and productionresponse of mustard ( Brassica juncea L. ) as guano and rabbit urine given. The research startedfrom november 2011 until january 2012. The design use randomized block design factorial with 2aspect. The first aspect is guano consist of four stages those are G0 ( 0 g/plant ), G1 ( 4 g/plant ), G2( 8 g/plant ), G3 ( 12 g/plant ). The second factor is rabbit urine consist four stages those are U0 ( 0ml/L water ), U1 ( 20 ml/L water ), U2 ( 40 ml/L water ), U3 ( 60 ml/L water ). Guano givenperform real effect to plant height, number of leaf, leaf area, fresh weight per plant, dry weight perplant, production per plot, but not gave any influenced to production per hectare and harvest index.Rabbit urine given perform real effect to plant height, number of leaf, leaf area, fresh weight perplant, dry weight per plant, production per plot, but not gave any influenced to plant height at 2MST, number of leaf 2 MST, production per hectare and harvest index. The interaction betweenboth aspect influenced on plant fresh weight, dry weight, production per plot but not gave anyinfluenced to plant height, number of leaf, production per hectare and harvest index.Key word : guano, rabbit urine, mustard, growth and production